PENDIDIKAN KEWIRAUSAHAN SEBAGAI SOLUSI MENGATASI PENGANGGURAN TERDIDIK DI INDONESIA - Nur Asnawi (El-QUDWAH, 2014)
Oleh: Nur Asnawi Dosen Fakultas Ekonomi UIN Maulana Malik Ibrahim Malang  Abstract Unemployment as one of the macroeconomic indicators of a country is one of the important issues that must be considered, not least in Indonesia. Unemployment in Indonesia almost half donated by college graduates are huge numbers. Ironic phenomenon that emerged in the world of education in Indonesia is the higher one's education, the probability of becoming unemployed is higher. One of the solutions offered by the government to reduce unemployment is to create jobs with government bids model of entrepreneurial But this in certain circles, especially among the educated tend to avoid this profession choice. Average - The average interest in higher office job. It is based on the calculation of the costs that they spend for education and expect a rate of return (rate of return) are comparable.